Теоретико-прикладні засади ефективності відновлення авіаційної техніки - Калиновський, А. О.; Калиновська, Н. Л.; Шемеляк, А. Р.; Kalynovskyi, A.; Kalynovska, N.; Shemelyak, A. (Видавництво Львівської політехніки, 2022)
Досліджено особливості визначення сучасними науковцями поняття ефективності. Розкрито зміст ефективності через показники рентабельності. Досліджено трактування ефективності як певного стану справ. Виділено особливості розуміння ефективності як міри досягнення цілей, співвідношення між установленою метою та отриманими результатами. Узагальнено підходи науковців щодо трактування поняття ефективності, а також, враховуючи розкриті особливості діяльності з відновлення авіаційної техніки, сформульовано основні положення, які доцільно покласти в основу формулювання визначення ефективності відновлення авіаційної техніки. Вивчення літературних джерел засвідчило існування різних видів ефективності. Встановлено що ефективність, на думку багатьох науковців, буває економічна та соціальна. Досліджено класифікації ефективності окремих проєктів або видів діяльності. З огляду на це, запропонована типізація ефективності процесу відновлення авіаційної техніки авіаремонтними підприємствами з метою розроблення критеріїв та методів її оцінювання.

The results of the enterprise's economic activity are multifaceted and depend on many factors. Under such conditions, it becomes more and more difficult to evaluate the obtained results of the enterprise activity. This is especially difficult to do in the aviation industry, since the complexity of aviation equipment and the tragic consequences of its malfunction significantly complicate the calculation of the economic efficiency of the aviation equipment restoration. For a better understanding of the problem, it is necessary to comprehensively reveal theoretical approaches and identify the most important factors for evaluating the effectiveness of aviation equipment restoration. In order to solve the above problem, the purpose of the article is established as a study of the theoretical and applied principles of the effectiveness of the aviation equipment restoration. To realize this goal, the main tasks of the article are a deeper interpretation of the features of the concept of "efficiency", highlighting the views of modern authors on the issue and finding common denominators in their views, as well as developing a typification of the effectiveness of the process of restoring aircraft equipment by aircraft repair enterprises. The peculiarities of the definition of the concept of efficiency by modern scientists have been studied. The meaning of efficiency is revealed through profitability indicators. The interpretation of efficiency as a certain state of affairs has been studied. Features of the understanding of efficiency as a measure of achieving goals, the relationship between the established goal and the obtained results are highlighted. The approaches of scientists regarding the interpretation of the concept of efficiency are summarized, and also, taking into account the revealed features of the activity on the restoration of aviation equipment, the main provisions are formulated, which should be used as a basis for the formulation of the determination of the efficiency of the restoration of aviation equipment. The study of literary sources proved the existence of various types of efficiency. It has been established that efficiency, according to many scientists, is economic and social. The classification of the effectiveness of individual projects or types of activities was studied. Taking this into account, it is proposed to typify the efficiency of the process of restoration of aircraft equipment by aircraft repair enterprises in order to develop criteria and methods of its evaluation.
Theoretical and applied principles of the efficiency of aviation equipment restoration
Keywords: ефективність; ефект; витрати; оцінювання; результат; авіаційна техніка; відновлення; якість; efficiency; effect; costs; evaluation; result; aviation equipment; recovery; quality; 629.73.083; 338.47-044.3(477)